Curriculum Integration: Optimizing Multiple Intelligence of Children - Arini, Shoofi Dwi; Mudjito, Mudjito; Hariyati, Nunuk (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2021)
This research described curriculum integration on optimizing multiple intelligence of early childhood education. This research was case study with qualitative descriptive approach. Data were collected by interview, observation, and documentation. The data were collected then analyzed and triangulated and member checked for validation. The results showed that children’s intelligence can be optimized by learning method integrated with tauhid values in every of six development aspect, moral and religious value, cognitive, language, physical-motor, social-emotional, and art. The school that becomes subject for this research was using center-based classroom and habituation learning method.